Eksplorasi Potensi Akasia (Acacia nilotica) (L.) Willd ex Del. sebagai Spesies Bioprospektif dalam Rangka Pemanfaatan Sumber Daya Alam Hayati secara Lestari - Djufri Djufri (Universitas Syiah Kuala, 2009)
The objectives of this research are to study character of A. nilotica includes morphology description, anatomy, and ecology (life cycle, spreading and seed production in BNP, stand structure, soil condition, and association of species). Research method used to know cycle life, spreading and seed production in BNP and the done conducted stand structure with direct perception in field. Produce seed used a square method having a nest counted 10 squares by using plastic. Obtained stand structure data with model is Permanent Square for the width of 20 x 20 m of counted 15 squares and at each square measured by a diameter and high counted 10 trees. Analysis of association used contingency table, and Influence of salinity to soil used result of laboratory analysis. Conclusion from this research are (1). There are six step life cycle of A. nilotica that is seed corps, seedling, juvenile, adult, flower, and seed in pod, (3). Stand structure of A. nilotica in BNP pertained as straightened age, (4). There are three of species positive association to A. nilotica is bayapan (Brachiria reptans), rumput gunung (Oplismenus burmanii), dan rumput kawat (Dactyloctenium aegyptium), (5). The analysis of soil fertility parameter indicates that there symptom of effect treatment salinity concentration at test soil, (6). Treatment salinity concentration has an effect to organ damage A. nilotica, specially on root, bark, and leaf. So that at 14 HST of most crop test has died the effect unable to tolerate tried treatment.